The diversity and susceptibility against antibiotics of Salmonella spp. clinical isolates from Yogyakarta, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Kurniati E, Retnaningrum E, Wijayanti N, Wibawa T. 2022. The diversity and susceptibility against antibiotics of Salmonella spp. clinical isolates from Yogyakarta, Indonesia. Biodiversitas 23: 5806-5813. Salmonella spp. are bacteria that causes enteric fever. Salmonella infection is a serious burden in both developed and developing countries, including Indonesia. Because of infrastructure limitation, Salmonella spp. infection treatment mostly based on clinical observation without proper identification of the causative bacteria. Although the clinical manifestation of the diseases is difficult to distinguished, it is believed that Salmonella spp. diversity is high in the community. This work aims to analyze the diversity of Salmonella spp. and their susceptibility against antibiotics. The Salmonella spp clinical isolates obtained from three clinical laboratories were subjected to cultivation, phenotypic characterization, and further biochemical and molecular characterization. Biochemical properties of strains were analyzed, whereas protein profiles were analyzed using the SDS-PAGE method. The molecular characterization was carried out by sequencing of 16S rRNA encoded gene. Numeric-phenetic clustering analysis of the 18 Salmonella spp clinical isolates showed that, they were allocated to two large clusters, namely Cluster I and Cluster II. Reconstruction of the phylogeny tree of the 18 clinical isolates and the reference strains showed that all of them belonged to one clade, namely the Salmonella enterica subsp. Enterica. However, it was recognized also six sub-clades. The antibiotic susceptibility pattern of Salmonella spp. revealed that practically all antibiotics (80%) had a high proportion of susceptibility, except for cefazoline, gentamicin, and amikacin, which have zero susceptibility. Numeric-phenetic clustering analysis combined with phylogeny tree reconstruction showed the diversity of Salmonella spp. circulating in Yogyakarta with alarming signal of certain antibiotic resistance.
Keywords: Antibiotic resistance, numeric-phenotypic, phylogenetic 16S rRNA, Salmonella spp